Introduction of Nature Exploration Activities through a Deep Learning Approach in Enhancing Children’s Creativity at TK Aisyiyah 3 - Santun Nurraihan; Sukrin Sukrin; Wahyu Mulyadi (Journal of Education and Teacher Training Innovation, 2026)
This study aims to examine the introduction of nature exploration activities through a deep learning approach in enhancing children's creativity at TK Aisyiyah 3. The research employs a qualitative descriptive method involving teachers and early childhood learners as participants. The learning intervention is designed through experiential and meaningful activities, where children directly interact with natural environments to stimulate curiosity, critical thinking, and creative expression. Data were collected through observation, interviews, and documentation of learning processes and children's work. The findings indicate that the implementation of deep learning-based nature exploration activities significantly improves children's creativity, as reflected in their ability to generate ideas, solve simple problems, and express themselves through various forms of activities. Among the indicators of creativity, initiative and originality emerged as the most prominent improvements, as children increasingly demonstrated spontaneous participation in activities, proposed unique ideas, and explored natural objects in diverse and imaginative ways. Furthermore, children demonstrate higher engagement, enthusiasm, and independence during the learning process. This study suggests that integrating nature exploration with a deep learning approach can create meaningful learning experiences and effectively foster creativity in early childhood education.